2019
DOI: 10.1088/1757-899x/698/6/066029
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring assigned fatigue gamma percentage of the components

Abstract: The problem of increasing the efficiency of the construction machines functioning continues to be relevant in modern conditions. The downtime of construction equipment, in particular, of a single-bucket excavator (SBE), leads to a violation of the terms of work and to significant economic losses. One of the most loaded elements of a single-bucket excavator is a boom. Increasing the reliability of its work reduces the number of the machine failures greatly, and as a result reduces the cost of repairs and equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…In previously published works [8][9][10][11][12][13] there is information about the formation of the surface layer in the process of vibration processing in the environment of metallic working media. These processes are accompanied by plastic deformation of the surface layers of the metal under conditions of multiple dynamic contact of particles of the working medium with the part.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously published works [8][9][10][11][12][13] there is information about the formation of the surface layer in the process of vibration processing in the environment of metallic working media. These processes are accompanied by plastic deformation of the surface layers of the metal under conditions of multiple dynamic contact of particles of the working medium with the part.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…The morphology of vibrational chemical-mechanical oxide layer: T=20 min, AA=2 mm, scale is 100 nm Studies of the surface morphology of a vibrational chemical-mechanical oxide coating revealed the growth stages and dimensions of the oxide film obtained as a result of the deposition of an AL9 grade aluminum alloy on a polished surface under modes: vibration amplitude A = 2 mm and frequency f = 33 Hz, time 5, 10, 20 min[10][11][12][13]. The original aluminum surface is shown inFig.…”
mentioning
confidence: 99%
“…In most cities of the Rostov region for the period 2008-2016 there is an increase in the level of air pollution with soot, carbon monoxide, nitrogen oxides, nitrogen dioxide, phenol and formaldehyde, which is directly related to a significant increase in the fleet of vehicles in use. At the same time, there is a decrease in the level of pollution: sulfur dioxide, nitrogen oxides, hydrogen sulfide and benzopyrene, which clearly demonstrates the result of the decisions taken at the state level to restrict import of used cars and to improve quality of hydrocarbon fuels [7][8][9][10][11][12][13][14].…”
Section: Environmental Monitoringmentioning
confidence: 99%
“…The broad technological capabilities of vibrowave technological systems are the most effective means for obtaining high-quality, from the point of view of ensuring operational properties, coatings for various functional purposes on the surface [1][2][3][4][5][6][7][8][9][10][11][12]. Feature of the coating method considered in the article is that it is formed on the metal surface as a result of shock-pulse interaction of free-moving indenters in a closed volume under the influence of low-frequency oscillations.…”
Section: Introductionmentioning
confidence: 99%